A novel CD81 homolog identified in lamprey, Lampetra japonica, with roles in the immune response of lamprey VLRB+ lymphocytes. (26th September 2018) - Liang, Wenjing; Gao, Miceng; Song, Xueying; Han, Yinglun; Go, Meng; Su, Peng; Li, Qingwei; Liu, Xin
Abstract: The cluster of differentiation 81 (CD81), a member of the transmembrane 4 superfamily, is primarily found to be expressed in a wide variety of cells including T and B cells of vertebrates as a critical modulator. In the present study, the open reading frame of a CD81 gene homolog ( Lja-CD81 ) was cloned in lamprey, Lampetra japonica, which is 702 bp long and encodes a protein of 233-amino acids. Although Lja-CD81 seems to be close to CD9 molecules in their full-length sequences, Lja-CD81 possesses higher identity to vertebrates' CD81 than to CD9 (including a lamprey CD9) molecules in their large extracellular loops. In addition, it also possesses a myristoylation site (Met-Gly-Val-Glu-Gly-Cys-Leu-Lys) in its N-terminal region which is identical to the N-terminal regions of CD81 molecules. These data suggest that CD9 and CD81 molecules diverged no later than the emergence of jawless vertebrates. The mRNA levels of Lja-CD81 in lymphocytes and supraneural myeloid bodies were up-regulated significantly after stimulation with mixed antigens, and a similar expressional pattern of Lja-CD81 at protein level was also confirmed. Furthermore, Lja-CD81 was found to be co-localized with variable lymphocyte receptor B (VLRB) evenly on the cell membrane of peripheral blood lymphocytes isolated from control group, but they were found to aggregate on one side of the membrane of peripheral blood VLRB + lymphocytes after stimulation with mixed antigens. All these results indicate that the Lja-CD81 identified in lamprey may play an important role in the immune response of lamprey VLRB + lymphocytes.